(untitled) (Comprehensive Journal of Science, 2025)
This study aims to examine refugee rights from a comparative perspective between Islamic jurisprudence and international humanitarian law, through analyzing relevant Sharia texts and international conventions. The research adopts both the descriptive-analytical and comparative methodologies to highlight the points of convergence and divergence between the two frameworks, as well as their potential complementarity in protecting refugees. The findings reveal that Islamic jurisprudence preceded international law in establishing principles of protection and human dignity, whereas international law provided a more institutional and detailed framework for implementation. The study recommends developing contemporary Islamic legal interpretations that address modern challenges, strengthening national legislation in Muslim countries by integrating Sharia principles with international obligations, and enhancing cooperation between Islamic and international organizations to ensure broader and more effective protection for refugees.